ANALISIS KEPUASAN MAHASISWA TERHADAP SISTEM PEMBELAJARAN ONLINE BERDASARKAN END USER COMPUTING SATISFACTION (EUCS) SELAMA PANDEMI COVID -19 - Muhammad Helmy Reza; Fatana Suastrini (Idaarah: Jurnal Manajemen Pendidikan, 2022)
The Covid-19 pandemic has forced educational institutions to change the way they carry out the teaching-learning process. The process of teaching-learning activities has changed from face to face directly to teaching-learning in a network (online). The need for a system that can support this process change is urgently needed. Responding to this need, Mataram State Islamic University as an educational institution, utilizes its system, namely the Learning Management System (LMS) application. This study aims to analyze student satisfaction with the LMS application system, which is based on the End User Computing Satisfaction (EUCS) model. The type of research used in this research is quantitative research. The location of the research was carried out at the Mataram State Islamic University. The sample used in this study were 90 students. The analytical technique used in this research is descriptive statistical analysis. The results of this study indicate that students are quite satisfied with the LMS application system used to support the teaching-learning process.